Biodiversity, food and nutrition: A new agenda for sustainable food systems - Hunter, Danny; Borelli, Teresa; Gee, Eliot (Routledge, 2020)
This book examines the challenges and impacts of poor diets and nutrition from current food systems and the potential contribution of biodiversity and ecosystem services in addressing these problems. It also presents a multi-country, cross-sectoral analysis of initiatives that have promoted local food biodiversity in four countries: Brazil, Kenya, Turkey and Sri Lanka.